Bond strengths of orthodontic brackets to restorative resin composite surfaces - Lai Poon Y.; Woods Michael G.; Tyas Martin J. (Sciendo, 1999)
In orthodontic practice, it is not uncommon to bond brackets to resin composite restorations. With this in mind, this study was designed to compare first the shear/peel strengths of metal, ceramic and polycarbonate brackets bonded to microfilled resin composite (RC), using either a light-cured resinmodified gloss ionomer cement (Fuji Ortha LC), a chemical-cured composite (System 1 +) or a lightcured composite adhesive (Transbond XT); and then to examine the effects of thermacycling on the shear/peel strengths of these systems. Four different brackets were used: Iwo stainless steel (Victory and Optimesh), one ceromie (Transcend 6000) and one polycarbonate (Spirit MB) Seventy-two specimens of each bracket were divided inta three groups for bonding with one of the three adhesives. Half the specimens fram each group were also thermocycled. Mean shear/peel bond strengths were found to be significantly different for the faur different brackets, althaugh not influenced by the three adhesives used within each group. All graups were found to have clinically-acceptable mean bond strengths, except for Spirit MB-System l +. After thermocycling, both Optimesh-Transband XT and Victory-System l + groups shawed superior mean band strengths (26.8 and 24.4 MPa, respectively) when compared with all other groups (p<0.05). Applying the Weibull survival analysis for groups utilising Victory, Transcend 6000 and Spirit MB brackets, those with 90 per cent or greater probabilities of survival included Victory-System l +, Transcend 6000-Fuji Ortho LC, Victory-Fuji Ortho LC and Spirit MB-Transbond XT groups. In all graups, band failure was mainly (64 per cent) cohesive within the RC restorative surface. The thermocycled Spirit MB-Transbond XT group hod the highest frequency of undamaged RC failure interfaces. Despite the focus of this study being on bond strength and the potential for surface damage, it was noted that these properties shauld always be considered alongside other factors such as the strength of the bracket itself, friction within the bracket siat, patients' wishes, cost of the materiols and the presenting malocclusion.